Exploring Key Factors of Application Software Services and Their Relationships for Organizational Success in SMEs. (6th August 2013) - Lee, Jung Sub; Kwon, Youngsun; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> This paper sets up an extended model that integrates the technology acceptance model and DeLone and McLean's information system success model and also extends this integrated model by adding a construct representing specific features of application services in order to investigate the way that features of application services influence small and medium‐sized enterprises' use of application services. Overall, the extended model performs well in explaining the relationships between constructs, and this research shows that certain specific features of application services are key factors that have positive effects on application service usage behavior and organizational success.